Appraisal of Road Transport Policy Reform in Nigeria: A Case of Infrastructural Deficit - Anthony Kayode Oroleye (Universitas Muhammadiyah Yogyakarta, 2019)
The study examined the road transport system reform in Nigeria. This was intending to assess the adequacy of road transport reform in Nigeria. The study employed both primary and secondary data. This study employed a stratified sampling technique for the choice of civil servants who are at directorate cadre with a total population of 35 in the Federal Ministry of Transport, Federal Ministry of Works and Federal Road Maintenance Agency. For interview administration, a purposive sampling technique was used to select the sample size of (FMW 3; FMT 2; FERMA 1) 6 Directors which constituted 17.1% who are the custodian of road transport policy. Observation of road infrastructures and office equipment was carried out. The secondary sources of information that were employed included relevant official publications and records from the Federal Ministry of Transport, Federal Ministry of Works and Federal Road Maintenance Agency who are a major player in road transport; journal articles, periodicals, and internet sources. Data collected through the use of the in-depth interview from the Directors of the two ministries and agency were analyzed using descriptive statistics such as percentages, tables, and frequency distribution and graphs. The results revealed that the road transport system reform in Nigeria was structurally deficient as it did not address all social classes especially the physically challenged and the elderly among others. The study concluded that as a result of hindrances associated with road transport reform the expected road infrastructure expansion and facilities upgrade through the reform recorded a partial success.